Population parameters and heterogeneity in survival rates of Indo-Pacific humpback dolphins in a heavily urbanized coastal region of southeast China: implications for conservation - Lin, Wenzhi; Karczmarski, Leszek; Chan, Stephen C. Y.; Zheng, Ruiqiang; Ho, Yuen-Wa; Mo, Yaqian (Frontiers in Marine Science, 2024)
The Pearl River Delta (PRD) region on the southeast coast of China is among the largest and most populated metropolitan regions of the world, subjecting the Indo-Pacific humpback dolphins (Sousa chinensis) inhabiting coastal waters of this region – apparently the largest population of this species – to intense anthropogenic pressure. In this 5-year study (2011-2015), we applied mark-recapture techniques to quantify population parameters of humpback dolphins in the main body of the extensive estuarine system of the Pearl River, the Lingding Bay (LB), the most urbanized and industrialized part of PRD. The super-population size was estimated at 928 individuals (95% CI=823-1046), which however over-represents the latest number of extant animals. Annual estimates fluctuated between 708 and 750 dolphins, and likely reflect most accurately the latest/current number of humpback dolphins in waters of LB. Both the overall and annual estimates generated by our study are considerably lower than previously published abundance estimates. Apparent survival rates were generally low, estimated at 0.943 (SE = 0.008, 95% CI = 0.929-0.958) and 0.815 (SE = 0.025, 95% CI = 0.766-0.866) for adults and juveniles, respectively. In conjunction with limited recruitment, they may have led to a substantial decline in population numbers over the past two decades. Notably, dolphins exhibited heterogeneous apparent survival rates across the complex anthropogenic seascape of LB. Adult individuals that use Hong Kong waters as their primary habitat exhibited 6.2% higher survival rates than those in other parts of LB. This difference tripled (19.2%) for juveniles, a likely expression of their susceptibility to environmental and/or anthropogenic stresses. We suggest that the difference in survival is largely due to heterogeneous anthropogenic stressors that vary spatially across the estuary, among which habitat loss, pollution, and declining prey resources appear to be the primary threats. Based on our latest findings, we call for a strategic conservation planning with the highest priority given to preserve the remaining key dolphin habitats in Hong Kong waters, and to quantify and mitigate the impacts of major stressor(s) in Guangdong (mainland China) waters. Given the encroachment of ever-more-intense human activities on the coastal habitats of humpback dolphins, understanding their demographic response and the underlying mechanisms of the population processes may prove instrumental in the formulation of a conservation management strategy that can secure their continuous survival.